A Perspective on the Success and Failure of BCG - Kumar, Pawan (Frontiers in Immunology, 2021)
TB continues to be one of the major public health threats. BCG is the only available vaccine against TB and confers significant protection against the childhood disease. However, the protective efficacy of BCG against adult pulmonary TB, which represents the larger burden of disease, is highly variable. It has been suggested that prior exposure to environmental mycobacteria (EMb) mitigates the anti-TB efficacy of BCG by blocking its duplication or masking its immunogenicity. The of BCG against childhood TB and failure of repeated BCG administration to provide additional benefit against adult pulmonary TB, however, is suggestive of some other mechanisms for the failure of BCG against the adult pulmonary disease. Importantly, TB is a heterogeneous disease occurring in different forms and having distinct mechanisms of pathogenesis. While inability of the immune system to contain the bacilli is responsible for TB pathogenesis in infants, an aggravated immune response to Mtb has been blamed for the development of adult pulmonary TB. Available data suggest that EMb play a key role in heightening the immune response against Mtb. In this article, differential efficacy of BCG against childhood and adult TB is explained by taking into account the heterogeneity of TB, mechanisms of TB pathogenesis, and the effect of EMb on anti-Mtb immunity. It is believed that a refined understanding of the success and failure of BCG will help in the development of effective anti-TB vaccines.